Selective detection of hypochlorous acid in living cervical cancer cells with an organoselenium-based BOPPY probe. (1st September 2022) - Shelar, Divyesh S.; Malankar, Gauri S.; M., Manikandan; Patra, Malay; Butcher, Ray J.; Manjare, Sudesh T.
Abstract : The synthesis and crystal structure of the first selenium-containing BOPPY probe. The probe is selective for exogenous and endogenous HOCl detection in HeLa cells with a "turn-on" fluorescence response. Abstract : The first organoselenium-containing BOPPY-based small molecular probe was synthesized and the structure was elucidated by NMR and single-crystal X-ray diffraction. The probe presents high selectivity and sensitivity towards hypochlorite ions over other reactive oxygen species. It showed fast response with a good detection limit (0.15 μM) for hypochlorite ions. The probe was able to detect endogenous hypochlorite in the human cervical cancer cell line (HeLa) by fluorescence microscopy with good biocompatibility. The probe also showed reversibility with biothiols such as GSH, Cys, Hcy and NAC.